Cissus sicyoides phytotherapy as complementary to the treatment of type II diabetes mellitus (International Seven Journal of Health Research, 2024)
Diabetes Melitus (DM) has become a public health issue in recent years. The comorbidities that affect their sufferers lead to a reduction in daily activities, a worsening of quality of life and an increase in mortality as a result of illnesses and complications of the disease. Basic health units, together with their health promotion programs and prevention strategies, have been adapting protocols for comprehensive care for patients with diabetes mellitus, guiding them towards a healthier lifestyle. This work showed the benefits of the complementary use of phytotherapy, specifically Cissus sicyoides in patients with diabetes mellitus, demonstrating hypoglycemic effects in 50% of patients subjected to the use of the dry extract. Adjunct to the treatment of diabetes mellitus II there is a need to implement strategies that reinforce the use of herbal therapies and research needs to be carried out to this end.